Ethics, Integrity and Policymaking The Value of the Case Study - O'Mathúna, Dónal; Iphofen, Ron (Research Ethics Forum,, 2022)
This Open Access book provides illustrative case studies that explore various research and innovation topics that raise challenges requiring ethical reflection and careful policymaking responses. The cases highlight diverse ethical challenges and provide lessons for the various options available for policymaking. Cases are drawn from many fields, including artificial intelligence, space science, energy, data protection, professional research practice and pandemic planning. Case studies are particularly helpful with ethical issues to provide crucial context. This book reflects the ambiguity of ethical dilemmas in contemporary policymaking. Analyses reflect current debates where consensus has not yet been achieved. These cases illustrate key points made throughout the PRO-RES EU-funded project from which they arise: that ethical judgement is a fluid enterprise, where values, principles and standards must constantly adjust to new situations, new events and new research developments. This book is an indispensable aid to policymaking that addresses, and/or uses evidence from, novel research developments.